Application of Time-Out Strategies to Reduce Tantrum Behavior in Children With Autism Spectrum Disorder (ASD) - Monika Nur Edlina; Mumpuniarti Mumpuniarti; Muhamad Aflaha Rijal; Hanifa Mutharah; Cindy Rahmi Aulia; Anisa Sri Rizky (FKIP - Universitas Riau, 2026)
This study aimed to reduce tantrum behavior in students with Autism Spectrum Disorder (ASD) through the implementation of a structured time-out strategy in a Special School (SLB). The research was motivated by the high frequency, duration, and intensity of tantrums that significantly disrupted the learning process, while existing behavior-management practices were largely reactive and unstructured. Using a Classroom Action Research (CAR) design, the study was conducted in three cycles consisting of planning, action, observation, and reflection. The participants were two students with ASD who frequently exhibited tantrum behavior. Data were collected through structured observations, interviews with teachers and parents, and documentation, and were analyzed using qualitative and quantitative approaches with triangulation to ensure data credibility. The findings showed a consistent reduction in tantrum frequency, duration, and intensity across the three cycles. By the final cycle, tantrum intensity decreased from moderate–severe to mild. The study concludes that the time-out strategy is an effective and practical intervention for managing tantrum behavior in students with ASD in special school settings.